The E3 Ubiquitin Ligase NEDD4L Targets OGG1 for Ubiquitylation and Modulates the Cellular DNA Damage Response - Hughes, Jonathan R.; Parsons, Jason L. (Frontiers in Cell and Developmental Biology, 2020)
8-oxoguanine DNA glycosylase (OGG1) is the major cellular enzyme required for the excision of 8-oxoguanine DNA base lesions in DNA through the base excision repair (BER) pathway, and therefore plays a major role in suppressing mutagenesis and in controlling genome stability. However, the mechanism of regulation of cellular OGG1 protein, particularly in response to oxidative stress, is unclear. We have purified the major E3 ubiquitin ligase responsible for OGG1 ubiquitylation from human cell extracts, and identify this as E3 ubiquitin-protein ligase NEDD4-like (NEDD4L). We demonstrate that recombinant NEDD4L stimulates ubiquitylation of OGG1 in vitro, particularly on lysine 341, and that NEDD4L and OGG1 interact in U2OS cells. Depletion of NEDD4L in U2OS cells has no impact on the stability and steady-state protein levels of OGG1, however OGG1 stability is enhanced in response to oxidative stress induced by ionising radiation. Furthermore, ubiquitylation of OGG1 by NEDD4L in vitro inhibits its DNA glycosylase/lyase activity. As a consequence of prolonged OGG1 stability and increased excision activity in the absence of NEDD4L, cells display increased DNA repair capacity but conversely that this decreases cell survival post-irradiation. This effect can be reproduced following OGG1 overexpression, suggesting that dysregulation of OGG1 increases the formation of lethal intermediate DNA lesions. Our study therefore highlights the importance of balancing OGG1 protein levels and BER capacity in maintaining genome stability.